PENGARUH KOMITMEN DOSEN TERHADAP PERGURUAN TINGGI YANG EFEKTIF - Christie Kusnandar (Journal of Accounting and Management Innovation, 2019)
Many lecturers are no longer committed to building effective universities, because they are burdened with social problems that have not been resolved properly, such as lecturers' lack of harmony with both leaders and peers; unbalanced personal life; welfare; psychological state and others. As a result most of the lecturers at the time of carrying out the task not because of his call, but for the needs of fulfillment of life. This condition has a significant impact on the expected quality of education, because educated generations experience confusion and anxiety when lecturers lose focus with their vocation.Keywords: Commitment, Effective College